Instagram-Based Infographics on the Transitional Period to the New Order, 1965-1966: Enhancing Learning Interest Among Students at Ungaran Public High School - Kamajaya Dwi Dharma Prasetyo (Indonesian Journal of History Education, 2024)
Learning interest is influenced by two main factors: internal factors, which consists of attention, attitude, talent, and ability; and external factors, which consists of teacher engagement during the learning process, the availability of learning facilities and infrastructure, parental guidance in home education, and environmental conditions. Several problems were found in the observations and interviews conducted by SMA Negeri 2 Ungaran (a high school) researchers. These problems include the development of learning media that could be more optimal, the use of social media is less controllable, and the disruption of students' interest in learning from the use of social media. Social media is the primary influence on students' interest in learning. This results in students consuming more social media than listening to learning from teachers in the classroom. The research method used is Research and Development (R&D) with a development model from Thiagarajan called 4D (Four D), namely Define, Design, Development, and Disinterested. The initial stage of this research is analyzing the needs of teachers and students regarding the needs of learning media, and then product design is carried out. The product development stage is carried out by feasibility tests by validators who are experts in materials, media, and learning practitioners. The last stage is to distribute the product through Instagram social media. The study results show that Instagram infographics impact students' interest in learning the history of students in grade XII.7 of SMA Negeri 2 Ungaran by 59%.